Prevalence and review of pathological anatomy of gestational choriocarcinoma in Ibadan (2022)
Objectives: Gestational choriocarcinoma (GCC) is a highly malignant epithelial tumor arising from the trophoblast of any type of gestational event, most often a complete hydatidiform mole. Choriocarcinoma is the most aggressive form of gestational trophoblastic neoplasia owing to their rapid growth and metastatic potential. This study reviewed all cases of GCC seen at the University College Hospital Ibadan. Methods: This was a 20 year retrospective hospital-based study designed to review all histologically diagnosed cases of choriocarcinoma registered at the Department of Pathology, University College Hospital (UCH), Ibadan, Nigeria, from 1st January, 1997 to 31st December, 2016. Clinicopathological data was extracted from the departmental surgical day book, Ward register, Department of Medical Records and Cancer Registry. The data was analyzed using the Statistical Package for Social Sciences, version 22. The results were presented in tables, relative frequencies and group percentages. Results: One hundred and eighty three cases of gestational trophoblastic disease were histologically diagnosed within the study period out of which 36 cases were GCC accounting for 19.7%. 55.6% of all the cases were received as endometrial biopsies, 33.3% as hysterectomy specimens, 8.3% as cervical biopsies and 2.8 as an anterior vaginal wall mass. Choriocarcinoma occurred in the age range 20 to 50 years with majority of cases occurring in the third decade of life. Conclusion: Gestational choriocarcinoma is still the most common gestational trophoblastic neoplasia seen in our environment. Awareness of this tumour with a high index of suspicion is needed for an accurate diagnosis and patient management.